A Re-Reading on the Emergence of the Indian Nationalist Movement and their Immense Contributions (Global Journal of Human-Social Science, 2019)
Indian Nationalist Movement is known to be the greatest freedom movement against the colonial power in world History. However, the younger generations tend to forget their immense contributions to free India which they have today. India was never free since the Aryan invasion and was under the British colonial rule for around 200 years until her independence in 1947. Before the colonization, the Indians were divided based on their castes, creed, regions, religions, etc. Until the arrival of the British in the soil of India, national consciousness did not emerge among the Indians. They were fighting against each other to expand their territory and for their interest. However, with the advent of the B.E.I.C. and colonizing the Indian Territory, the B.E.I.C. became the tools for the Indian nationalism. Due to the social, political and economic condition under the rule of British, the people struggle against the British to regain their national identity. In one way, the British colonization was a curse for the Indians. However, on the other hand, it became a way of uniting the Indians for creating India as a Nation.
Keywords: beic; british; imperialist; india/indians; nationalist/nationalism; and colonization